A study of femoral bicondylar angle in Udaipur, India zone - Shrivastava, Bhavana; Mehta, Rupali; K., Prabhakaran; Jain, L. K. (International Journal of Research in Medical Sciences, 2020)
Background: Human body consists of 206 bones; among which femur. The thigh bone is considered as the biggest and strongest bone of the body. The bone contains a femoral bicondylar angle which helps in maintaining the balance and certain movements of the body. Those movements are essential to stand upright and erect; therefore, helps in balancing the posture of the body. Bicondylar angle shows various gestures and characteristics essential for describing the necessary ailments of the human skeleton. Thus, the present study is designed with an aim to measure and compare the bicondylar angle of femur both in males and females in Udaipur, Rajasthan, India zone. Methods: Totally, 96 bones were studied- 48 males and 48 females’ bones in 2 years duration. The study was carried out in the Department of Anatomy of Geetanjali Medical College and Hospital and R.N.T. Medical College. The bicondylar angle was measured with a suitable apparatus comprising of compass, Digital Vernier Calliper, scale and protector (Figure 1) along with osteometric board. Bicondylar angle of male and female bone was calculated using SPSS software. Results: The study shows that the bicondylar angle of left femur was greater than right femur in both the genders, but their side differences was statistically insignificant (p>0.05). Conclusions: Hence, the bicondylar angle of female is larger than in comparison to males and these results can put emphasis/light on the orthopaedic clinicians and surgeons to know the etiology of osteometric diseases.